(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article explores the influence of historical events on the poetry of two renowned Romantic poets, Lord Byron and Mikhail Lermontov. By examining the political and social contexts in which these poets lived and wrote, this study aims to demonstrate how their works were shaped by the tumultuous events of their time. Through a comparative analysis of selected poems, we uncover how Byron and Lermontov responded to themes such as revolution, war, exile, and nationalism in their poetry. By delving into the historical background of their works, this article sheds light on the ways in which these poets engaged with and reflected upon the pressing issues of their era.